Design a CPW antenna on rubber substrate for multiband applications - Sakib, Nazmus; Ibrahim, Siti Noorjannah; Ibrahimy, Muhammad Ibn; Mohamad, Sarah Yasmin; Mahfuz, M. M. Hasan (Springer, 2022)
This paper presents a compact CPW monopole antenna on rubber substrate for multiband applications. The multiband applications (2.45 and 3.65 GHz) are achieved on this antenna design with better antenna performances. Specially this antenna focused on ISM band application meanwhile some of slots (S1, S2, S3) have been used and attained another resonant frequency at 3.65 GHz for Wi-MAX application. The achievement of the antenna outcomes from this design that the bandwidth of 520 MHz for first band, the second band of 76 MHz for Wi-MAX application and the radiation efficiency attained around 90%. Moreover, the realized gain was 4.27 dBi at 2.45 GHz which overcome the most of existing design on that field. The computer simulation technology (CST) microwave studio has been used for antenna simulation.